The Influence of Motivation on Employee Performance in the Investment and One-Stop Service Office of Manokwari Regency - Ayomi, Yafeth Williams; Yertas, Maria; Lambi, Manuel (Economics and Digital Business Review, 2024)
This study aims to analyze the effect of motivation on employee performance at the Manokwari Regency Investment and One-Stop Integrated Service Office. Motivation is essential in increasing employee productivity and work efficiency, ultimately impacting public service quality. The research employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to 50 DPMPTSP staff respondents. Simple linear regression techniques were used to analyze the data and measure how motivation affects employee performance. The results indicate that motivation positively and significantly influences employee performance, with a coefficient of determination of 65%. This suggests that higher employee motivation is associated with better performance. The study recommends managing motivation through sustainable training, reward, and career development programs to improve employee performance and support optimizing public services in Manokwari Regency. The findings of this study provide valuable insights into the importance of employee motivation in enhancing public sector performance. By understanding the relationship between motivation and employee performance, policymakers and managers can develop effective strategies to foster a motivated and high-performing workforce, ultimately leading to improved public service delivery in the Manokwari Regency.